Study of Gaming Disorder and Its Association with Depressive Disorder and Anxiety among Medical Students in India - Hanee Patel; Niraj Pandit; Rudra Patel; Ishita Gupta; Dhairya Jain; Shreya Katoch (Annals of Indian Psychiatry)
Context: Internet gaming disorder (IGD) was included in the 5th edition of The Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Addiction to Internet gaming is prevalent among Indian medical students. This study aims to measure the severity and pattern of gaming behavior along with the impact and association of IGD on different psychological conditions such as depression and anxiety. Methods: A cross-sectional study was conducted through an online survey among 845 medical students at a tertiary care teaching hospital in India. The Internet GD Scale-Short Form (IGDS9-SF) was used to assess the intensity of gaming disorders, while patient health questionnaire-9 (PHQ-9) and generalized anxiety disorder assessment (GAD-7) were used to assess the severity of depression and anxiety, respectively. Results: A total of 194 students were identified as current gamers, out of which 36 had gaming disorders based on DSM-5 diagnostic criteria for IGD from the current study sample. Multiple regression was calculated for the following age (B = 0.85, P = 0.002), weight (B = 0.07, P = 0.02), average time spent on gaming/day in hours (B = 1.01, P < 0.0001), PHQ-9 scores (B = 0.35, P ≤ 0.0001), GAD-7 scores (B = −0.24, P = 0.01) - Model R2 = 0.35, F = 19.41, P < 0.0001. Conclusions: Potentially problematic gaming was found to be associated with psychological symptoms, negative affectivity, and a preference for solitude. There is a need for other studies that can help in creating awareness about the prevalence of gaming disorders in medical students.